Discovery of Diphenylacetamides as CXCR7 Inhibitors with Novel β-Arrestin Antagonist Activity - Menhaji-Klotz, Elnaz (ACS Med Chem Lett, 2020)
[Image: see text] The atypical chemokine receptor CXCR7 has been studied in various disease settings including immunological diseases and heart disease. Efforts to elucidate the role of CXCR7 have been limited by the lack of suitable chemical tools with a range of pharmacological profiles. A high-throughput screen was conducted to discover novel chemical matter with the potential to modulate CXCR7 receptor activity. This led to the identification of a series of diphenylacetamides confirmed in a CXCL12 competition assay indicating receptor binding. Further evaluation of this series revealed a lack of activity in the functional assay measuring β-arrestin recruitment. The most potent representative, compound 10 (K(i) = 597 nM), was determined to be an antagonist in the β-arrestin assay (IC(50) = 622 nM). To our knowledge, this is the first reported small molecule β-arrestin antagonist for CXCR7, useful as an in vitro chemical tool to elucidate the effects of CXCL12 displacement with β-arrestin antagonism in models for diseases such as cardiac injury and suitable as starting point for hit optimization directed toward an in vivo tool compound for studying CXCR7 receptor pharmacology.